2015
DOI: 10.1371/journal.pone.0130484
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment with Annexin A1 Reduces Atherosclerotic Plaque Burden in LDLR-/- Mice on Western Type Diet

Abstract: ObjectiveTo investigate therapeutic effects of annexin A1 (anxA1) on atherogenesis in LDLR-/- mice.MethodsHuman recombinant annexin A1 (hr-anxA1) was produced by a prokaryotic expression system, purified and analysed on phosphatidylserine (PS) binding and formyl peptide receptor (FPR) activation. Biodistribution of 99mTechnetium-hr-anxA1 was determined in C57Bl/6J mice. 12 Weeks old LDLR-/- mice were fed a Western Type Diet (WTD) during 6 weeks (Group I) or 12 weeks (Group P). Mice received hr-anxA1 (1 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 57 publications
3
44
0
Order By: Relevance
“…*p < 0.05 cardiomyopathy and nephropathy. Previously, both full-length AXNA1 and the Ac2-26 peptide (the N-terminal functional fragment of ANXA1) have been used in vivo and both elicit biological function [17][18][19]). In this study, we chose to use fulllength hrANXA1, as the dose of full-length ANXA1 needed to induce biological function is up to 20 times less than that of the Ac2-26 peptide [36] and 14 times less than that needed to induce changes in gene expression in terms of molarity [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…*p < 0.05 cardiomyopathy and nephropathy. Previously, both full-length AXNA1 and the Ac2-26 peptide (the N-terminal functional fragment of ANXA1) have been used in vivo and both elicit biological function [17][18][19]). In this study, we chose to use fulllength hrANXA1, as the dose of full-length ANXA1 needed to induce biological function is up to 20 times less than that of the Ac2-26 peptide [36] and 14 times less than that needed to induce changes in gene expression in terms of molarity [37].…”
Section: Discussionmentioning
confidence: 99%
“…in 0.9 mol/l citrate buffer, 5 days, n = 8), while sham mice received vehicle only (10 ml/kg, 0.9 mol/l citrate buffer i.p., 5 days, n = 8). hrANXA1 was produced and purified as previously published [18]. Treatment groups received either prophylactic treatment (weeks 1-13 after STZ administration, n = 6), treatment during STZ administration (days 1-5, n = 6) or therapeutic treatment (weeks 8-13 after STZ administration, n = 6) with hrANXA1 (1 μg, 100 μl, 50 mmol/l HEPES; 140 mmol/l NaCl; pH 7.4, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,13 Of note, it has been demonstrated that arterial-specific nanodelivery of Ac2-26 could be a promising tool to prevent atheroprogression, a strategy that may also be applicable to treatment of angioplasty-related side effects. 14 In line with previously successfully used FPR2 ligands, 3 stents coated with AnxA1 protein could potentially be suitable to prevent lumen loss and inflammation after arterial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Ac2-26 peptide derived from Annexin A1 has strong pro-resolution effects in vivo; however, further studies need to be performed to elucidate its role in macrophage polarization. One recent study found that full-length Annexin A1 increased IL-10 secretion and decreased the M1 macrophage phenotype [78] whereas another study found that Annexin A1 did not appear to contribute to macrophage polarization [79]. …”
Section: Delivering Molecules To Control Macrophage Polarizationmentioning
confidence: 99%